Reverse Phase High Performance Liquid Chromatographic Method for the Analysis of Racecadotril in Pharmaceutical Dosage Forms - Laha, T.K.; Patnaik, R.; Choudhury, S.; Sen, S. (Asian Journal of Chemistry, 2010)
A rapid and sensitive reverse phase HPLC method is applied for the qualitative and quantitative assay of racecadotril in pharmaceutical dosage forms. Racecadotril was chromatographed on a reverse phase C18 column with a mobile phase consisting of acetonitrile:methanol:water in the ratio of 50:40:10 (v/v/v). The mobile phase was pumped at a flow rate of 1 mL/min. Sildenafil was used as an internal standard and the eluents were monitored at 217 nm. The retention time of the drug was 3.168 min. With this method, excellent linearity was observed in the concentration range of 10-70 μg/mL. LOD (lower limit of detection) and LOQ (lower limit of quantification) were found to be 0.05 and 0.14 ppm, respectively. The recovery of analytes after extraction from formulations using the described method was 99.65 ± 0.77 %. The method was found to be applicable for analysis of drug in tablets. The results of the analysis were validated statistically.